2013
DOI: 10.1002/ar.22847
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Change in Sulcal Length Asymmetry in Cerebrum of Cynomolgus Monkeys (Macaca fascicularis)

Abstract: The purpose of this study was to determine the timing of the onset of adult-type sulcal length asymmetry during postnatal development of the male cynomolgus monkey cerebrum. The monkey brain has already reached adult size by 3 months of age, although the body weight only represents 1/8 of the adult body weight by that time. The fronto-occipital length and the cerebral width also reached adult levels by that postnatal age with no left/right bias. Consistently, lengths of the major primary sulci reached adult le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…In our previous neuroanatomical study, a greater cortical convolution in males than in females was observed in the visual cortical area of ferrets following the completion of the primary sulcal emergence (Sawada and Watanabe, 2012 ). A regional pattern of sulcal length asymmetry was acquired in human males from adolescence to young adulthood (Blanton et al, 2001 ; Clark et al, 2010 ), as well as in cynomolgus monkeys (Sakamoto et al, 2014 ), and enhancement of sulcal length asymmetry in prefrontal and perisylvian regions during adolescence was more prominent in males than in females in humans (Blanton et al, 2001 ; Clark et al, 2010 ). Thus, sex-related change in the cortical convolution may occur at Stage 4 of the gyrification process (during adolescent to young adult periods), although its characteristics will vary depending on the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous neuroanatomical study, a greater cortical convolution in males than in females was observed in the visual cortical area of ferrets following the completion of the primary sulcal emergence (Sawada and Watanabe, 2012 ). A regional pattern of sulcal length asymmetry was acquired in human males from adolescence to young adulthood (Blanton et al, 2001 ; Clark et al, 2010 ), as well as in cynomolgus monkeys (Sakamoto et al, 2014 ), and enhancement of sulcal length asymmetry in prefrontal and perisylvian regions during adolescence was more prominent in males than in females in humans (Blanton et al, 2001 ; Clark et al, 2010 ). Thus, sex-related change in the cortical convolution may occur at Stage 4 of the gyrification process (during adolescent to young adult periods), although its characteristics will vary depending on the species.…”
Section: Discussionmentioning
confidence: 99%
“…While sexual dimorphism of the sulcal morphology has not been fully addressed, an asymmetric pattern of the primary sulcal length is known to differ between sexes in humans (Liu et al, 2010 ) and cynomolgus monkeys (Imai et al, 2011 ). The male adult pattern of sulcal length asymmetry in those primates was acquired during adolescence to young adulthood (Clark et al, 2010 ; Sakamoto et al, 2014 ). Also, age-related changes in sulcal morphology are more prominent in males than in females (Kochunov et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain ECF-to-CSF clearance (Cl csf ) could not be estimated with precision, and so was fixed 2.9 ml/min in rats and 0.6 ml/min in NHPs on the basis of preliminary naïve pool analyses. These estimates are approximately an order of magnitude larger than the reported ECF bulk flows in the two species: 0.2 ml/min in rats (de Lange, 2013) and 22 ml/min in NHPs, the latter estimate scaled from the rat value using brain weight allometry [70 g brain weight for a 5 kg animal (Sakamoto et al, 2014)]. The difference is attributed to D-amphetamine clearance into nerve terminals by DAT (Sulzer et al, 2005) and metabolism in the brain, including N-hydroxylation by brain flavin-monooxygenase (Cashman et al, 1999).…”
Section: Resultsmentioning
confidence: 89%
“…6). While myelination of the cerebral cortex continued to increase during adolescence to adulthood in humans (Miller et al, 2012;Shafee et al, 2015), the adult-type sulcal morphology was acquired after adolescence in humans (Clark et al, 2010) and cynomolgus monkeys (Sakamoto et al, 2014). Gyrification abnormality has been reported in human neurodevelopmental disorders such as autism (Nordahl et al, 2007;Schaer et al, 2013;Auzias et al, 2014) and schizophrenia (Gay et al, 2013;Budday et al, 2014).…”
Section: Discussionmentioning
confidence: 99%